PENERAPAN MOTIF BATIK JAMBI TAMPUK MANGGIS PADA DESAIN FURNITUR HOTEL SEBAGAI UPAYA DESAIN YANG BERKELANJUTAN: Application of Jambi’s Tampuk Manggis Batik Motive on Hotel Furniture Design as a Sustainable Design Effort - Christianto Roesli (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
Indonesia has a very diverse variety of decorative batik motives. In general, the resulting batik motifs are a combination of shapes, colours and images based on the environment, culture, natural potential, and the influence of the local community where the batik is made. In addition, the batik makers not only create visually beautiful batik, but also provide beauty through the meaning that is in every batik motif they create. This research discusses one of the Indonesian batik motifs from Jambi, namely Tampuk Manggis which is a source of Indonesian cultural heritage that has the potential to be an inspiration for furniture designs in hotel. The purpose of this research is to explore design by applying the Tampuk Manggis– Jambi’s batik motive in furniture design and focus on preserving Indonesian culture and sustainable design that can be applied in hotel. This research uses the Goal Grid method as a sorter that carried out four guidelines; what must be achieved, what must be maintained, what must be avoided, and what must be eliminated. The results of this research are expected to be useful for industry practitioners and designers who aim to create memorable guest experiences and promote cultural values and sustainability